Ambidextrous leadership and change‐oriented organizational citizenship behavior: Mediating role of psychological safety. Issue 1 (17th August 2020) - Iqbal, Zafar; Ghazanfar, Faheem; Hameed, Filza; Mujtaba, Ghulam; Swati, Mudassar Anwar
Abstract : The study aims to empirically test the role of ambidextrous leadership on change‐oriented organizational citizenship behavior through psychological safety (PS). The role of leadership is important in cultivating employee's creative behavior. To test our hypothesized model, we have collected data from the textile industry of Pakistan in which 175 leader‐follower dyads were selected as sample. The data were collected in two‐time lags to avoid social desirability bias. Causal attribution theory was used to test the model and structural equation modeling has been used for data analysis. We have found full mediation of PS in the relationship between ambidextrous leadership and change‐oriented organizational citizenship behavior. Theoretical and managerial implications along with limitations and future direction are discussed.